Meningkatkan Kineja Guru Dalam Pembelajaran Melalui Supervisi Klinis - Suwadi (Education Research Center, 2025)
This study highlights the role of the principal as an effective leader in improving teacher competence through classroom supervision activities at SDN Domas 1 Gresik. An effective principal not only understands the problems faced by teachers but also provides support and services tailored to their needs, both individually and in groups. By allowing room for creativity development and encouraging innovative ideas, the principal plays a crucial role in enhancing teacher performance. Moreover, the principal, as a supervisor, acts as a dynamic consultant who guides and motivates teachers to improve their teaching abilities and adapt to changes and developments in the education sector. This study applies the School Action Research (PTS) method, focusing on increasing teacher motivation and competence in preparing Lesson Plans (RPP) through continuous guidance. Various learning tools such as lesson plans, teaching aids, data collection techniques, and evaluation instruments were developed to assist teachers in classroom management and lesson evaluation. The results show that continuous guidance positively impacts the improvement of teacher motivation and competence in preparing lesson plans. Observations revealed a significant increase in teacher competence, with the average score of lesson plan components rising from 69% in the first cycle to 83% in the second cycle, indicating a 14% increase. These findings suggest that a continuous guidance approach is effective in enhancing the quality of teachers' lesson preparation, ultimately contributing to improved learning quality in schools.